Management of Orbital Complications Based on Chandler Classification Stage II-IV in Pediatric Sinusitis: A Systematic Review - Fadelia Meutia Ananda; Syifa Safira Nabila Putri; Aisyah Muthmainnah Budu; Nuzulina Safira Hapsari Sunanto (Fakultas Kedokteran Universitas Muslim Indonesia, 2026)
Background: Orbital complications are the most common sequelae of pediatric sinusitis (70–85%) and can lead to vision loss or intracranial issues if untreated. Irreversible vision loss occurs in 3–11% of advanced cases. Objective: To review current evidence on medical versus surgical treatment for Chandler Stage II–IV orbital complications in pediatric sinusitis, particularly since there is no clear guideline on when urgent surgery is required and when antibiotics alone are sufficient. Methods: A systematic review (2015–2025) was conducted via PubMed, Scopus, and ScienceDirect. Included studies involved patients <18 years with Stage II–IV complications. Data on treatments, outcomes, and risk of bias (Newcastle–Ottawa Scale) were analyzed. Results: Thirty-three studies (>16,700 patients) were included. Stage II was successfully treated with antibiotics alone in >90% of cases. In Stage III, 35–50% required surgery, especially with abscess ≥3.6 mm, vision changes, or poor response to antibiotics. Stage IV nearly always required urgent surgery. Stage-based treatment improved vision, motility, and proptosis, with no reported deaths. Conclusion: Chandler staging effectively guides treatment. Antibiotics suffice for Stage II; surgery is often needed for Stage III–IV. Timely, evidence-based care helps prevent permanent vision loss.